Stalky & Co. - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2002)
"Stalky & Co." by Rudyard Kipling is a novel published in 1899. Set at a British boarding school based on Kipling's own experience, it follows three cynical boys who approach authority and patriotism with knowing irreverence. Through tales of pranks, revenge, and elaborate schemes against housemasters and bullies, these stories subvert idealized school fiction with hints of violence, the macabre, and worldly awareness. The final chapter reveals how their mischievous training served them as adults in the British Empire's armed forces. (This is an automatically generated summary.)
In ambush -- Slaves of the lamp, pt. I -- An unsavory interlude -- The impressionists -- The moral reformers -- A little prep -- The flag of their country -- The last term -- Slaves of the lamp, pt. II.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Stalky_%26_Co.
Release date is 2002-01-01
A. Elizabeth Warren, and David Widger
Keywords: Schools -- Fiction